Knowledge and practices of mothers regarding exclusive breastfeeding in the Mahwelereng local area of the Limpopo Province, South Africa - Frans, R. A.; Malema, R. N.; Matlala, S. F. (My University, 2015)
The aim of this study was to determine the knowledge and practices of exclusive breastfeeding and the challenges facing mothers in the Mahwelereng local area of Limpopo Province, South Africa. A simple random sampling method was used to select 275 mothers with babies younger than six months old from six primary health care clinics. A self-structured questionnaire was used for data collection. Less than half (74; 42.3%) of the mothers practised exclusive breastfeeding and 137 (78.3%) had been given information about exclusive breastfeeding. There is an association between knowledge of exclusive breastfeeding (Chi-Square= 14.039; Sig=0.000; p<0.05) and exclusive breastfeeding practice. There is no association between exclusive breastfeeding practice and HIV status (Chi-Square=2.444; Sig=0.118; p>0.05). Challenges that mothers faced in relation to practising exclusive breastfeeding were work, school and health-related and,-pressure from family to mix-feed. However, 42.9% of the respondents indicated that they did not have any challenges with regard to the practice of breastfeeding. One-on-one counselling about exclusive breastfeeding needs to be intensified and maternity leave should be extended from four to six months. The majority of respondents showed adequate knowledge of what exclusive breastfeeding was because they had been counselled about breastfeeding although they were not practising it.
African Journal for Physical, Health Education, Recreation and Dance (AJPHERD) December 2015 (Supplement 1:4), pp. 812-825.
Keywords: Exclusive breastfeeding; Mix-feeding; Mothers and breastfeeding; Breast feeding -- South Africa